Level of self-esteem among Muslim medical students and its association with religiosity - Aminuddin, Amirah; Mustapa, Nurul Fitri; Abdul Hadi, Azwanis; Zainal Abidin, Muhammad 'Adil (USIM, 2021)
Medicine is one of the most difficult study course and profession that faces many psychological challenges. A high level of self-esteem is needed to cope with such challenges, and religiosity is seen as one of the approaches to increase one’s self-esteem especially among Muslim physicians. Aims & Objectives: This study aims to measure the level of self-esteem among medical students and its association with religiosity. Methodology: This online cross-sectional study was conducted among 178 International Islamic University Malaysia (IIUM) Kuantan medical students using validated 10- items IIUM Religiosity Scale (IIUMReIS), and 10-items Rosenberg Self-Esteem Scale (RSES). Descriptive statistics was used to measure the level of self-esteem while chi-square, Mann-Whitney U test, Spearman’s correlation, univariate, and multivariate logistic regression were used to explore the association between self-esteem with the predictors. Results and findings: More than half of the students (58.5%) have a high level of self-esteem. They scored an average of 35 (IQR = 6) in terms of religiosity. Those with higher religiosity were predicted to have significantly high self-esteem (r = 0.345). Other significant factor includes frequency of supererogatory prayer where daily practice has 0.3 lower odds of having low self-esteem. (95% CI = 0.11, 0.85, p = 0.05) Majority of the students have a high level of self-esteem. Implications suggest the role of religiosity and the impact of supererogatory prayer. Early and consistent strengthening of self-esteem via motivational, spiritual, and religious programs may be advisable